1998
DOI: 10.1038/bjc.1998.23
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the rhoC gene correlates with progression of ductal adenocarcinoma of the pancreas

Abstract: Summary It has been reported that the rho genes, which consist of a ras-related small GTPase protein family, regulate cytoskeletal structures and have the potential to transform cultured cells. To investigate the biological relevance of the rho genes in pancreatic carcinogenesis, we examined expressions of the rhoA, B and C genes by polymerase chain reaction after reverse transcription (RT-PCR) in 33 cases of ductal adenocarcinoma of the pancreas. In addition, mutations of the K-ras, rhoA, B and C genes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
245
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(255 citation statements)
references
References 24 publications
8
245
1
1
Order By: Relevance
“…Rho-family GTPases function in cytoskeletal reorganization, cell migration, stress fiber formation and focal adhesion [137]. It is not surprising that enhanced expression of one of the Rho GTPase family members, RhoC, correlates with the progression of various tumor types to a metastatic phenotype [138,139]. In gene expression profiling experiments with melanoma variants of low or high metastatic potential, RhoC has been identified as a candidate involved in the spread of malignant cells.…”
Section: Genes Mediating Metastasismentioning
confidence: 99%
“…Rho-family GTPases function in cytoskeletal reorganization, cell migration, stress fiber formation and focal adhesion [137]. It is not surprising that enhanced expression of one of the Rho GTPase family members, RhoC, correlates with the progression of various tumor types to a metastatic phenotype [138,139]. In gene expression profiling experiments with melanoma variants of low or high metastatic potential, RhoC has been identified as a candidate involved in the spread of malignant cells.…”
Section: Genes Mediating Metastasismentioning
confidence: 99%
“…The quality was checked in 1% agarose gels and the concentration was measured using an ultraviolet Spectrophotometer (Biochrom Ltd, Cambridge, England) (Suwa et al, 1998). The UV wavelength was adjusted at 260 nm.…”
Section: Rna Isolationmentioning
confidence: 99%
“…Recently, emerging data suggest that RhoC gene may have a potential role in carcinogenesis and metastasis of tumour cells (Itoh et al, 1999;Clark et al, 2000). The expression level of RhoC in metastatic region of pancreatic cancer has been previously reported to be higher than primary lesion (Suwa et al, 1998). In addition, a genomic-wide analysis of gene expression revealed that RhoC gene was involved in vascular invasiveness of HCC (Okabe et al, 2001).…”
mentioning
confidence: 99%
“…Previous studies demonstrated that aberrant expression and activation of Rho small GTPases are important in tumor generation and progression, although mutation of Rho GTPase genes rarely occurs in tumors (Keely, 2001;Boettner and Van Aelst, 2002). Elevated expression of RhoA, RhoC, Rac1B and Rac2 were found in a variety of cancers including head and neck squamouscell cancers, ductal adenocarcinomas of the pancreas, inflammatory breast cancer cells, colon cancers and lung cancers (Suwa et al, 1998;van Golen et al, 2000;Abraham et al, 2001). Aberrant expression of Rho and Rac have been found in even moderately differentiated tumors, suggesting that Rho proteins may be early markers of tumor progression (Moscow et al, 1994;Suwa et al, 1998).…”
Section: Tc10 Contributes To V-rel-mediated Transformationmentioning
confidence: 99%
“…Elevated expression of RhoA, RhoC, Rac1B and Rac2 were found in a variety of cancers including head and neck squamouscell cancers, ductal adenocarcinomas of the pancreas, inflammatory breast cancer cells, colon cancers and lung cancers (Suwa et al, 1998;van Golen et al, 2000;Abraham et al, 2001). Aberrant expression of Rho and Rac have been found in even moderately differentiated tumors, suggesting that Rho proteins may be early markers of tumor progression (Moscow et al, 1994;Suwa et al, 1998). This report provides the first evidence that the overexpression of TC10 results in transformation of primary cells in culture.…”
Section: Tc10 Contributes To V-rel-mediated Transformationmentioning
confidence: 99%